Factors Influencing Malaysian Tourists’ Brand Loyalty towards Jakarta as a Tourist Destination - Dita, Sari Kristiani (2011)
Tourism industry is now recognized as one of the important industry which is experiencing growth and able to survive in the midst of economic crisis. So many countries are currently vying each other to promote their respective tourism industries as one of the source country’s income. The objective of this research is to get better understanding on what Malaysian tourists’ perception towards Jakarta as a tourist’ destination and how influence factors impacting on Malaysian tourists’ brand loyalty. The influencing factors that are implemented in this research are attractiveness, value, quality and risk of tourist destination. Questionnaires are disseminated to 200 Malaysian tourists who have been to Jakarta and several SPSS software has been used to analyze the results. The research findings show that value of Jakarta has a high influence on Malaysian tourists’ brand loyalty. The results also show that overall factors have a positive influence toward Malaysian tourists’ brand loyalty. Further recommendations and discussions of the results for further research are also provided.